Offensive/defensive talent and sporting success in football: evidence from the big five European leagues - Carreras-Simó, M.; García, J. (Journal of Sports Economics, 2022)
Over the past decade, the sustained growth of the football business has been associated with clubs` interest in investing in players` talent, which has boosted both the transfer market and players` salaries. However, players` talent is heterogeneous, given that both defensive and offensive talent are required. Therefore, clubs have to decide on the optimal talent composition, taking into account the differences in the cost and the productivity of both talents. The article shows that, firstly, clubs` talent composition (ratio between offensive and defensive talent) presents significant differences over time among the Big Five European leagues. Secondly, the talent composition is consistent with maximizing sporting performance (or profit maximization) in the case of Serie A, but not in the case of Bundesliga. Results for Premier League, LaLiga and Ligue 1, are not conclusive with a few exceptions associated with the top teams.